Hispanic Garum at a Burnum Table (Archaeologia Adriatica, 2011)
In the excavations of the amphitheatre which was part of the Roman military camp at Burnum, a fragmentarily preserved amphora of the Dressel 8 type was found with a well preserved inscription (titulus pictus), confirming that the amphora served for the transport of hispanic garum, the famous fish sauce. In his paper, the author analyses the case from the typological and epigraphic aspects, discusses the significance of its unearthing in a military camp, and sets it in the context of other similar finds in the Adriatic region and surrounding areas.
Keywords: Burnum; amphora; Dressel 7-11; garum; titulus pictus